Morocco - Public Financial Management Performance Report (PEFA) : Assessment of Public Financial Management Systems, Procedures, and Institutions - World Bank (World Bank, 2012)
This Public Financial Management Performance Report (PFM-PR) assesses the current performance of financial management in Morocco's public sector. The Public Expenditure and Financial Accountability (PEFA) framework applied for this review uses an assessment tool based on a set of high-level indicators that provide reliable information on the performance of PFM systems, processes and institutions. The purpose of using this tool is to measure performance for five PFM areas in Morocco as compared to international standards. The Kingdom of Morocco is a medium-income country with a population of 31 million and per capita income of European Union (EU) 2,300 (2007). Average life expectancy has significantly improved to 72.4 years in 2007, reflecting a progressive improvement in living standards. Nonetheless, major social challenges remain, in particular the economic insecurity of a large segment of its residents. Despite a considerable improvement in poverty indicators during this century (the incidence of poverty fell from 15.3 percent in 2001 to 9 percent in 2007), more than a quarter of the population in 2007 remained economically vulnerable. The report covers public expenditure at the central government level, including central government's financial relationships with local and regional governments and with public enterprises (PE). Morocco has a relatively large public sector that accounts for 53 percent of gross domestic product (GDP) (2007), comparable to that for other Magreb countries.